The Influence of System Dynamics Resource Sharing on Collaborative Manufacturing Efficiency—Based on the Multiagent System and System Dynamics Method - Zhu, Xiaoxia; Guo, Xu; Liu, Hao; Li, Shuang; Zhang, Xiaohong (Frontiers in Psychology, 2022)
To improve the problems of inconvenient communication in the manufacturing industry, the ineffective use of resources, and the inability to efficiently complete manufacturing tasks, resource sharing has become an important model to promote the transformation and upgrading of the manufacturing industry. We use multiagent modeling to construct a resource-sharing model and take Baosteel as the micro background and the manufacturing industry as the macro background. Under this model, we discover the effect of resource sharing on the efficiency of intelligent manufacturing under network collaboration through system dynamics research. We build and simulate a dynamic model of system dynamics that couples the two backgrounds and give policy suggestions according to the simulation result.